LOW-TEMPERATURE THERMODYNAMIC PROPERTIES OF DISORDERED ZEOLITES OF THE NATROLITE GROUP - Paukov I.E.; Moroz N.K.; Kovalevskaya Yu.A.; Belitsky I.A. (My University, 2002)
The heat capacity of paranatrolite and tetranatrolite with a disordered distribution of Al and Si atoms has been measured in the temperature range of 6–309 K using the adiabatic calorimetry technique. The composition of the samples is represented with the formula (Na1.90K0.22Ca0.06)[Al2.24Si2.76O10]·nH2O, where n=3.10 for paranatrolite and n=2.31 for tetranatrolite. For both zeolites, thermodynamic functions (vibrational entropy, enthalpy, and free energy function) have been calculated. At T=298.15 K, the values of the heat capacity and entropy are 425.1 ± 0.8 and 419.1 ±0.8 J K−1 mol−1 for paranatrolite and 381.0 ± 0.7 and 383.2 ± 0.7 J K−1 mol−1 for tetranatrolite. Thermodynamic functions for tetranatrolite and paranatrolite with compositions corrected for the amount of extraframework cations and water molecules have also been calculated. The calculation for tetranatrolite with two water molecules and two extraframework cations per formula yields: C p (298.15)=359.1 J K−1 mol−1, S(298.15) −S(0)=362.8 J K−1 mol−1. Comparing these values with the literature data for the (Al,Si)-ordered natrolite, we can conclude that the order in tetrahedral atoms does not affect the heat capacity. The analysis of derivatives dC/dT for natrolite, paranatrolite, and tetranatrolite has indicated that the water- cations subsystem within the highly hydrated zeolite may become unstable at temperatures above 200 K.